Controlled oxidation of cobalt nanoparticles to obtain Co/CoO/Co3O4 composites with different Co content - Lozhkomoev, Aleksandr S.; Pervikov, Alexander V.; Kazantsev, Sergey O.; Suliz, Konstantin V.; Veselovskiy, Roman V.; Miller, Andrey A.; Lerner, Marat I. (Nanomaterials)
The paper studies patterns of interaction of electroexplosive Co nanoparticles with air oxygen during heating. The characteristics of Co nanoparticles and composite Co/CoO/Co3O4 nanoparticles formed as a result of oxidation were studied using transmission electron microscopy, X-ray phase analysis, thermogravimetric analysis, differential scanning calorimetry, and vibrating sample magnetometry. It was established that nanoparticles with similar morphology in the form of hollow spheres with different content of Co, CoO, and Co3O4 can be produced by varying oxidation temperatures. The influence of the composition of composite nanoparticles on their magnetic characteristics is shown.